Translational-rotary frequency up conversion vibration based energy harvesting device for human body motion - Putra, Azma; Ramlan, Roszaidi; Suhaimi, Khalis (Trans Tech Publications, 2014)
This paper presents some preliminary studies on the frequency-up conversion method for low frequency application energy harvesting device, mainly from human body motion, by employing the translational-rotary mechanism. Vibration signals from different parts of the human body were first measured when the human subject was walking at 5 km/h and jogging at 9 km/h. The signals obtain from the test was then reconstructed using Fourier Transform and it was found that frequency content of human body motion was in the range of 1 Hz – 25 Hz.. A preliminary experiment was conducted to check on the ability of the mechanism to amplify the excitation frequency. Although the experiment was not optimized, the device was able to amplify input frequency up to 3.6 times.